Practical derivations of fermion and gauge boson reduction formulae in curved spacetimes - Huhtala, Jesse; Vilja, Iiro (Springer Nature, 2025)
LSZ-type reduction formulae are derived for gauge fields and fermions in curved spacetime. The formulae are derived using a conserved current method applicable also to flat spacetimes. The method generalizes to more general quantum field theories. The formulae are then applied to a couple of basic problems to illustrate their use.